2003
DOI: 10.1021/jf034708j
|View full text |Cite
|
Sign up to set email alerts
|

Viridepyronone, a New Antifungal 6-Substituted 2H-Pyran-2-one Produced by Trichoderma viride

Abstract: A new antifungal 6-substituted 2H-pyran-2-one, named viridepyronone, has been isolated from a cultural filtrate of a strain of Trichoderma viride showing antagonistic activity in vitro toward Sclerotium rolfsii, which is the causal agent of crown and stem rot of artichoke. Viridepyronone was characterized as 6-(4-oxopentyl)-2H-pyran-2-one 2 with spectroscopic methods. Bioassays showed that viridepyronone had a good antifungal activity against S. rolfsii, and its minimum inhibitory concentration (over 90% inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 10 publications
2
46
0
1
Order By: Relevance
“…The phytotoxic metabolite from Lasiodiplodia pseudotheobromae used during the current study had no adverse effect on the tested crop, but showed a bioherbicidal effect on all the tested weeds. Some authors have also reported similar results from the use of fungal phytotoxic metabolite (Evidente et al, 2003).…”
Section: Discussionsupporting
confidence: 58%
“…The phytotoxic metabolite from Lasiodiplodia pseudotheobromae used during the current study had no adverse effect on the tested crop, but showed a bioherbicidal effect on all the tested weeds. Some authors have also reported similar results from the use of fungal phytotoxic metabolite (Evidente et al, 2003).…”
Section: Discussionsupporting
confidence: 58%
“…Recently, viridepyronone (18) was isolated from a cultural filtrate of a strain of T. viride. This compound showed antagonistic activity in vitro against Sclerotium rolfsii at a MIC of 196 lg/ml (>90% inhibition) (Evidente et al 2003).…”
Section: Simple Pyronesmentioning
confidence: 97%
“…Pyrones, related to pyridiones, and epoxy group are structural features which play an important role in the biological activity of some classes of naturally occurring compounds such as some substituted pyrones, 103,104 sequiterpenes eremophilanes, 105 trichothecenes, verrucarins and cytochalasins, [106][107][108] and sphaeropsidones. 50 Therefore, the marked reduction or the total loss of both phytotoxic and antifungal activities of two isomeric 4-hydroxy-6-methyl-2-pyridone derivatives 24 and 25 ( Fig.…”
Section: S Sapinea (Isolated From An Infected Cypress Tree) Toxinsmentioning
confidence: 99%